Direct and Indirect Measurements of Sex Hormones in Rodents During Fear Conditioning. Issue 5 (5th May 2021) - Florido, Antonio; Perez‐Caballero, Laura; Velasco, Eric Raúl; Molina, Patricia; Marin‐Blasco, Ignacio; Andero, Raül
Abstract: Fear conditioning (FC) is a widely accepted tool for the assessment of learning and memory processes in rodents related to normal and dysregulated acquired fear. The study of sex differences in fear learning and memory is vast and currently increasing. Sex hormones have proven to be crucial for fear memory formation in males and females, and several methods have been developed to assess this hormonal state in rats and mice. Herein, we explain a routine FC and extinction protocol, together with the evaluation of sex hormonal state in male and female rodents. We explain three protocols for the evaluation of this hormonal state directly from blood samples extracted during the procedure or indirectly through histological verification of the estrous cycle for females or behavioral assessment of social hierarchies in males. Although females have typically been considered to present great variability in sex hormones, it is highlighted that sex hormone assessment in males is as variable as in females and equally important for fear memory formation. The readout of these protocols has had a great impact on different fields of fear learning and memory study and appears essential when studying FC. The proven interaction with drugs involved in the modulation of these processes makes sex hormone assessment during FC a valuable tool for the development of effective treatments for fear‐related disorders in men and women. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Fear conditioning and fear extinction Basic Protocol 2 : Blood collection for direct measurement of sex hormone levels in fear conditioning Basic Protocol 3 : Indirect measurement of sex hormones in females during fear conditioning Basic Protocol 4 : Assessment of dominance status in males before a fear conditioning protocol Support Protocol : Construction of a confrontation tube